Quantitative evaluation of the enamel caries which were treated with casein phosphopeptide-amorphous calcium fluoride phosphate - Yazıcıoğlu, Oktay; Yaman, Batu Can; Güler, Ali Umut; Koray, Fatma (Medknow Publications & Media Pvt Ltd, 2017)
Objectives: The aim of this in vivo study was to quantitatively evaluate the remineralization of the enamel caries on smooth and occlusal surfaces using DIAGNOdent, after daily application of casein phosphopeptide-amorphous calcium fluoride phosphate (CPP-ACFP). Materials and Methods: Thirty volunteers, aged 18u30 years, with white spot lesions on the smooth and occlusal surfaces of the teeth were included in the study. These white spot lesions were visually examined and the degree of demineralization was quantitatively evaluated using DIAGNOdent. Volunteers with lesions scored as enamel caries on smooth surfaces (n = 109) and on occlusal surfaces (n = 176) were randomly divided into control and study groups. Both groups were instructed regarding oral hygiene and were asked to brush their teeth with the same tooth paste and tooth brush. In the study group, CPP-ACFP was applied daily for 4 min on the existing enamel caries lesions. After 4 weeks, the mineralization changes in enamel caries on the smooth and occlusal surfaces were assessed by DIAGNOdent. Recorded data were statistically analyzed by Wilcoxon signed-rank test and MannuWhitney U-test. Results: Comparison of DIAGNOdent values evaluated before and after the application of CPP-ACFP showed that the remineralization of enamel caries lesions on smooth and occlusal surfaces occurred in the study group (both, P < 0.001). The control group showed no quantitative changes at the end of 4 weeks (P > 0.05). At the end of the study period, the DIAGNOdent values differed significantly between the control and study groups (P < 0.001). Conclusions: Daily local application of CPP-ACFP for 4 min for 4 weeks results in significant remineralization of the initial caries lesions. Clinical Relevance: CPP-ACFP can be used in the treatment of white spot lesions.
WOS: 000407813400007
PubMed ID: 28656922
Keywords: Casein Phosphopeptide-Amorphous Calcium Phosphate; Fluoride; Noncavitated Caries Lesions; Remineralization